(untitled) - Krishnamurthy, N. (Boston, 2002)
Introduction to Computer Graphics was created by abridging and modifying that comprehensive teaching and reference work to suit the needs of different courses and different professional requirements. While this book is half the size of its parent, it is not merely a shorter version of it. Indeed, it features new material and, in some cases, a different approach to exposition, all added with the needs of its intended audience in mind.
Keywords: Computer graphics,Programming computer,Đồ hoạ máy tính,Chương trình máy tính